2021
DOI: 10.1515/jisys-2020-0060
|View full text |Cite
|
Sign up to set email alerts
|

Bangla hate speech detection on social media using attention-based recurrent neural network

Abstract: Hate speech has spread more rapidly through the daily use of technology and, most notably, by sharing your opinions or feelings on social media in a negative aspect. Although numerous works have been carried out in detecting hate speeches in English, German, and other languages, very few works have been carried out in the context of the Bengali language. In contrast, millions of people communicate on social media in Bengali. The few existing works that have been carried out need improvements in both accuracy a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Here, real IMDB and Amazon data sets were employed to estimate the suggested method performance. Similarly many approaches related to multi class sentiment classification [23][24][25][26][27] has been done in the previous studies but all those methods require better performance in terms of accuracy and the summary of literature review is presented in table 1 as shown below.…”
Section: Cognitive-inspired Domain Adaptationmentioning
confidence: 99%
“…Here, real IMDB and Amazon data sets were employed to estimate the suggested method performance. Similarly many approaches related to multi class sentiment classification [23][24][25][26][27] has been done in the previous studies but all those methods require better performance in terms of accuracy and the summary of literature review is presented in table 1 as shown below.…”
Section: Cognitive-inspired Domain Adaptationmentioning
confidence: 99%
“…Now the visual soft attention mechanism comes to play to classify the images based on the features obtained from the inceptionv3 model. The attention model is a streamlined attempt that focuses on the few relevant things of the selective activities [18]. As a result, this classification system focuses on human faces and determines whether or not the individual is wearing a mask.…”
Section: Facemask Detectionmentioning
confidence: 99%
“…Where V k represents k-time input, h k represents the hidden form at time k, and W kD represents k-time output [12].…”
Section: Recurrent Neural Network Analysismentioning
confidence: 99%